2011
DOI: 10.7863/jum.2011.30.8.1069
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Intracranial Arterial Stenosis Using Transcranial Color-Coded Duplex Sonography, Computed Tomographic Angiography, and Digital Subtraction Angiography

Abstract: Moderate agreement was found between CT angiography, transcranial color-coded sonography, and digital subtraction angiography in the evaluation of intracranial stenosis. Computed tomographic angiography and digital subtraction angiography are sufficient for assessment of the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 14 publications
2
18
0
3
Order By: Relevance
“…TCD has been proved effective to detect stenosis of intracranial large vessels, previous studies have shown substantial agreement of accuracy between TCD and digital subtraction angiography (DSA, 93.9%), as well as TCD and CT angiography (93.8%) for the evaluation of intracranial stenosis [25] . Compared with magnetic resonance angiography, TCD is cost-efficient and has therefore acquired increased popularity in China.…”
Section: Discussionmentioning
confidence: 99%
“…TCD has been proved effective to detect stenosis of intracranial large vessels, previous studies have shown substantial agreement of accuracy between TCD and digital subtraction angiography (DSA, 93.9%), as well as TCD and CT angiography (93.8%) for the evaluation of intracranial stenosis [25] . Compared with magnetic resonance angiography, TCD is cost-efficient and has therefore acquired increased popularity in China.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the measure of asymptomatic ICAS has been obtained from transcranial Doppler ultrasonography, which has a relatively lower sensitivity in identifying ICAS than brain CTA. 30 Why SBP in the early morning, compared with SBP at the other time of the day, was independently and most closely associated with cerebrovascular damage remains unexplained. Nonetheless, previous investigations provided some clues.…”
Section: Discussionmentioning
confidence: 99%
“…TCCS not only detects increased velocity of the blood flow, but also reveals disturbed flow caused by narrowing of the arterial lumen (Accorsi 2013). According to the previous studies, there is substantial agreement between TCCS and DSA (93.9%) and between TCCS and CT angiography (93.8%) for the evaluation of intracranial stenosis (Roubec et al 2011). Therefore, TCCS is a suitable tool for assessing IVAS and performing follow-up for interventional therapy.…”
Section: Discussionmentioning
confidence: 91%